Pengaruh Tingkat Kenyamanan Pengguna terhadap Keputusan Pembelian Kacamata - Setya Ferywidyastuti; Teguh Widihartono; R. Risang Haryo (STIKES HAKLI Semarang, 2025)
Glasses are an important need of people with the growth of increasing use. Consideration of user comfort is the determinant of purchasing decisions. The purpose of the study was to analyze the influence of user comfort level on the decision to purchase glasses. The study used a sample of 20 respondents using questionnaires and Field Research methods, which were carried out through observation in the field to obtain empirical information in accordance with existing reality. The nature of the research is qualitative descriptive, which is research that produces descriptive data to get an idea of the reality of certain social phenomena. The user's comfort level has a significant effect on the purchase decision, with indicators of refraction check (90%), lens type (85%), frame fitting (95%), and frame material (80%). The conclusion obtained from the study is that optical stores must increase the level of user comfort to increase sales.